2018
DOI: 10.1186/s13071-018-3132-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of tegumental damage to Schistosoma mansoni and S. haematobium after in vitro exposure to ferrocenyl, ruthenocenyl and benzyl derivatives of oxamniquine using scanning electron microscopy

Abstract: BackgroundSchistosomiasis is one of the most harmful parasitic diseases worldwide, praziquantel being the only drug in widespread use to treat it. We recently demonstrated that ferrocenyl, ruthenocenyl and benzyl derivatives of oxamniquine (Fc-OXA, Rc-OXA and Bn-OXA) are promising antischistosomal drug candidates.MethodsIn this study we assessed the tegumental damage of these three derivatives of oxamniquine using scanning electron microscopy. Adult Schistosoma mansoni and S. haematobium were exposed to a conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…For both prodigiosin and obatoclax, worm motility was not restored even after 72 hours recovery, contrasting significantly with results seen after praziquantel treatment where juvenile worms were found to have significantly better recovery after drug treatment than adult worms [48,49]. Imaging of prodigiosin and obatoclax treated worms revealed that both drugs resulted in significant damage to the tegument, with numerous areas of blebbing and separation from the worm body (Fig 3), a phenotype previously seen in with other anti-schistosomal drugs, and associated with increased ion flow across the tegument, exposure to host immune system, and eventual loss of viability [50,51].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 76%
“…For both prodigiosin and obatoclax, worm motility was not restored even after 72 hours recovery, contrasting significantly with results seen after praziquantel treatment where juvenile worms were found to have significantly better recovery after drug treatment than adult worms [48,49]. Imaging of prodigiosin and obatoclax treated worms revealed that both drugs resulted in significant damage to the tegument, with numerous areas of blebbing and separation from the worm body (Fig 3), a phenotype previously seen in with other anti-schistosomal drugs, and associated with increased ion flow across the tegument, exposure to host immune system, and eventual loss of viability [50,51].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 76%
“…This background inflammation is seen near veins and sinusoids, probably because of abundance of Schistosoma antigens following the treatment. The burst of antigens is a known phenomenon that may occur after treatment of schistosomiasis with anti-schistosomal drugs [37,38] or, similarly, filariasis treated with diethylcarbamazine [39]. In the placebo-treated mice there was a huge granulomatous inflammatory response that eventually led to mouse mortality (data not shown).…”
Section: Discussionmentioning
confidence: 98%
“…For comparison, by the same incubation time, juvenile S. mansoni incubated with 100 μM OXA and the control group showed no difference in the viability, confirming previous studies of OXA being only slightly active in vitro and against juvenile stages of the parasite. 9,24 Only by 72 h of incubation, where the derivatives had long exerted their activity, we found a 38% reduction of the viability of OXA respect to the control worms.…”
Section: Resultsmentioning
confidence: 65%
“…In vitro studies Fc-CH 2 -OXA, Rc-CH 2 -OXA and Ph-CH 2 -OXA previously demonstrated promising activity as drug candidates in vitro against adult S. mansoni and S. haematobium and first stage of the larval development (NTS: newly transformed schistosomula) and in vivo in adult S. mansoni infected mice. 22,24 In order to test the full potential of our compounds, we first elucidated the in vitro activity of the OXA derivatives against 28-day-old juvenile S. mansoni worms since one of the important drawbacks of PZQ is its missing activity against this developmental stage. All three compounds killed all the worms within 24 h of incubation at a concentration of 100 μM (Table 1).…”
Section: Resultsmentioning
confidence: 99%